2014
DOI: 10.1182/blood-2014-05-576041
|View full text |Cite
|
Sign up to set email alerts
|

Nonpermissive HLA-DPB1 mismatch increases mortality after myeloablative unrelated allogeneic hematopoietic cell transplantation

Abstract: Key Points High-resolution matching for HLA-A, -B, -C, and -DRB1 is required for optimal survival in myeloablative-unrelated donor transplantation. HLA-DPB1 nonpermissive mismatches should be avoided in otherwise matched transplants to minimize overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
222
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(249 citation statements)
references
References 33 publications
17
222
1
1
Order By: Relevance
“…Comparisons of the impact of single allele and single antigen mismatches on clinical outcome did not reveal significant differences, 5,11,12 except, possibly, for the HLA-C locus for which allele mismatches have been reported to be less detrimental than antigen mismatches. 18,20 However this could possibly be explained by the very high frequency (68.7%) of C*03:03/03:04 mismatches in the NMDP study.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 82%
See 2 more Smart Citations
“…Comparisons of the impact of single allele and single antigen mismatches on clinical outcome did not reveal significant differences, 5,11,12 except, possibly, for the HLA-C locus for which allele mismatches have been reported to be less detrimental than antigen mismatches. 18,20 However this could possibly be explained by the very high frequency (68.7%) of C*03:03/03:04 mismatches in the NMDP study.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 82%
“…15 The impact of HLA mismatches on overall mortality has been reported to be most apparent in patients with early disease. 12 In HSCT for non-malignant disorders single HLA-A, -B, -C or -DRB1 mismatches were not associated with acute or chronic GVHD but were associated with graft failure. 19 A large study of unrelated donor reduced-intensity conditioning HSCT based on 8/8 matching recently found that single HLA-A, -B, -C or -DRB1 mismatches were associated with a higher incidence of acute GVHD and a lower disease-free survival rate without differences in relapse rate or chronic GVHD.…”
Section: Impact Of Single Mismatchesmentioning
confidence: 97%
See 1 more Smart Citation
“…23 In the study of Pidala et al, among 8/8 matched cases, HLA-DPB1 and -DQB1 mismatches resulted in increased aG-VHD, and HLA-DPB1 mismatch had decreased relapse. 24 In the study of Fleischhauer et al, nonpermissive mismatches associated with higher risks of TRM compared to permissive mismatches or allele matches. 25 Another study from France, published by Gagne et al could only show an adverse prognosis in two HLA-DPB1 mismatches for severe aGVHD.…”
Section: Discussionmentioning
confidence: 98%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For instance, in the study by Loiseau et al reported increased frequency of severe aGVHD and poorer survival in two HLA-DP incompatibilities in a group of unrelated ASCT patients. 10 In this study they were not able show a significant relationship between HLA-DP mismatches and disease relapse.…”
Section: Discussionmentioning
confidence: 99%